2018
DOI: 10.1515/intag-2016-0092
|View full text |Cite
|
Sign up to set email alerts
|

Impact of monovalent cations on soil structure. Part II. Results of two Swiss soils

Abstract: A b s t r a c t. In this study, we investigated the impact of adding solutions with different potassium and sodium concentrations on dispersible clay, water retention characteristics, air permeability, and soil shrinkage behaviour using two agricultural soils from Switzerland with different clay content but similar organic carbon to clay ratio. Three different solutions (including only Na, only K, and the combination of both) were added to soil samples at three different cation ratio of soil structural stabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 40 publications
3
11
1
Order By: Relevance
“…The sensitivity to clay dispersion caused by adding monovalent cations is higher in soils with clay contents >15% than in soils with lower clay content (Levy and Torrento, 1995), and SDC generally increases with increasing clay content (Levy and Torrento, 1995;Etana et al, 2009). Similarly, in Part II of our series of papers (Farahani et al, 2018), we have found that clay dispersion was higher in a clay soil than in a silty loam soil.…”
Section: Resultssupporting
confidence: 67%
See 3 more Smart Citations
“…The sensitivity to clay dispersion caused by adding monovalent cations is higher in soils with clay contents >15% than in soils with lower clay content (Levy and Torrento, 1995), and SDC generally increases with increasing clay content (Levy and Torrento, 1995;Etana et al, 2009). Similarly, in Part II of our series of papers (Farahani et al, 2018), we have found that clay dispersion was higher in a clay soil than in a silty loam soil.…”
Section: Resultssupporting
confidence: 67%
“…Moreover, K ions within the diffuse double layer (DDL) probably increase DDL thickness, facilitating clay dispersion. In contrast, we found a smaller impact of K, compared to Na, on clay dispersion in Swiss soils in Part II of our study (Farahani et al, 2018). The dominant clay type in these soils was illite.…”
Section: Sdc (%)contrasting
confidence: 80%
See 2 more Smart Citations
“…Relationship between SAR or CROSS and exchangeable cations may vary because many soil factors, including pH, affect exchange reactions, and hence, the dispersive charge. In spite of including K and Mg effects in the formula, the relationship between CROSS and clay dispersion or hydraulic conductivity, although stronger than SAR, has been found to vary with soil factors [47,[52][53][54]. It is becoming clearer that clay dispersion in relation to CROSS depends on the dispersive charge of a given soil.…”
Section: Validity Of Models Based On Irrigation Water Qualitymentioning
confidence: 99%